Performance Evaluation of Dough Mixing Machine - Kunle Oni; Omowanle Akinmolayan; Adeyemi Mathew Ige (ABUAD Journal of Engineering Research and Development, 2025)
In bread-making, mixing is most crucial process to bring different ingredients together to achieve homogeneity, the quality of dough depends mainly on mixing processes. This study was carried out to evaluate the performance of dough mixing machine designed, by assessing the functional properties of wheat flour for the pasting properties and farinograph characteristics of the flour suitable for use in the mixing machine. A gear-driven electric motor of 1.23 kW maximum power supply with torque of 3.75 Nm was considered for the designed fabrication. The machine operated at 280 rpm with a mixing capacity of 31.9 kg/hr and an average efficiency of 94.7%. The dough mixer performance evaluation results analyzed for pasting property of the flour samples, indicated that flour from the Eagle Flour was the best for bread making with the value of peak viscosity of 792.1 RVU, trough viscosity of 193.6 RVU, breakdown viscosity of 598.5 RVU, setback viscosity of 73.9 RVU, final viscosity of 267.5 RVU, and pasting temperature of 50.2 oC. Result analysis shows that, Eagle Flour sample has a water absorption capacity, swelling capacity and bulk density of 152.69 %, 20.78 % and 0.78 g/ml respectively. Then, Farinograph characterized the mixing time, over mixing stability, and dough's rheological characteristics. The physical property of the bread obtained from fabricated dough mixer has a loaf volume of 1850 cm3, specific loaf volume of 4.19 cm3/g, density of 0.15 g/cm3 and oven spring of 0.16 mm. The overall acceptability rating of 94.28% and 89.48% were recorded for the bread from the fabricated and commercial dough mixers, respectively. Hence, 5 kilograms (kg) of components was able to mix properly and effectively in 8.15 minutes on average, which is 36.91 kilograms per hour. The fabricated dough mixer has a good market prospect.